2006
DOI: 10.1007/s10286-006-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of vagus nerve stimulation in epilepsy and implications for sudden unexpected death in epilepsy

Abstract: Vagus nerve stimulation (VNS) is a non-pharmacological therapy approved by the FDA for treatment of patients with partial-onset epilepsy. The most frequently encountered adverse effects typically occur during stimulation, are usually mild to moderate in severity, and resolve with reduction in current intensity or spontaneously over time. There are no apparent effects of VNS on vagally mediated visceral function. Though the precise mechanism of action of VNS remains unknown, available evidence suggests that cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 29 publications
2
9
0
1
Order By: Relevance
“…24 Another potential application of VNS in heart diseases is in the rate and rhythm control of AF. 10, 25, 26 VNS has been reported to reduce the incidence of sudden unexpected death in epilepsy (SUDEP), 1, 2 but others failed to confirm that finding. 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Another potential application of VNS in heart diseases is in the rate and rhythm control of AF. 10, 25, 26 VNS has been reported to reduce the incidence of sudden unexpected death in epilepsy (SUDEP), 1, 2 but others failed to confirm that finding. 27 …”
Section: Discussionmentioning
confidence: 99%
“…1, 2 Recent studies showed that there is significant interictal cardiac electrical instability (elevated T wave alternans) in patients with drug-resistant epilepsy, which was effectively suppressed by VNS. 3 Because T wave alternans is enhanced by sympathetic activation, 4 these findings suggest that VNS might be associated with reduced sympathetic tone.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Most patients are currently stimulated at 30 Hz, with a constant stimulation cycle of 30 seconds on and 5 minutes off. [26] Clinical trials have found the device to reduce the incidence of complex partial seizures in the majority of patients tested, with 20–40% of patients achieving a greater than 50% reduction in seizure frequency. [1133] The number of responders increases with time,[719] while the number of anti-epileptic drugs (AEDs) necessary to maintain satisfactory seizure control decreases after VNS.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent VNS with such a device has become a well-established, safe, and effective adjunct to medical therapyfor refractory epilepsy (Ben-Menachem, 2002; Schachter, 2006). Observations of mood elevation during VNS therapy for pharmacoresistant epilepsy (Ben-Menachem, 2002; Elger et al, 2000; Harden, 2002; Harden et al, 2000) suggested that such treatment might also show efficacy for refractory major depression.…”
Section: Introductionmentioning
confidence: 99%